THE INFLUENCE OF SOCIAL MEDIA PLATFORMS ON THE SOCIAL PSYCHOLOGICAL DEVELOPMENT OF THE PERSON - Muminova Nasiba Bozorovna (Bright Mind Publishing, 2025)
Social media platforms have now become an integral part of people's lives, and their development consists of several stages. Below we will consider the origin and stages of development of social media platforms.
Keywords: Social media, platforms, internet, computer, service.